ChemInform Abstract: Evidences of the Existence of SiTe2 Crystalline Phase and a Proposed New Si—Te Phase Diagram. Issue 24 (27th May 2016) - Mishra, R.; Mishra, P. K.; Phapale, S.; Babu, P. D.; Sastry, P. U.; Ravikumar, G.; Yadav, A. K.
Abstract: Si—Te alloys with compositions of 50—95 mol% Te are prepared by reaction of the elements in evacuated quartz ampoules (950 °C, 48 h; cooling to 25 °C at a rate of 3 °C/h).